knowledge strategic abilities And impact in the building of competitive advantage Field research the views of a sample of the administrative leaders of the Iraqi private banks - الكبيسي صلاح الدين عواد; ابراهيم تغريد خليل (Journal of Economics and Administrative Sciences, 2014)
The research synthesis variables of competitive advantage and the mechanism achieved by focusing on knowledge abilities and strategic of the administrative leadership, and governments and the developed countries took the racing frantically and my destiny to invest more money and resources to development of wealth and human knowledge is so choice investment winner always and who Aaikhyee never, because God Almighty give humans the abilities of all other creatures and that these abilities varying from person to person, there is the problem of search provoking questions about the essence of what it’s about research and both sides theoretical and field, the objective of this research to answer these questions through the framing of theoretical and conceptual all variables first and test models of the relationship and impact Secondly, the purpose of achieving the objective of this research and to answer questions about the problem, applied research on a sample of (70) manager in (9) banks Iraqi civil, was adopted resolution as an essential tool, as well as personal interviews to collect data and information that has been collected and analyzed using A number of statistical methods of ( frequencies, percentages, mean, standard deviation, coefficient of variation, and Spearman correlation coefficient, and analysis of simple and multiple regression, analysis of the track). The most prominent results were reached: There is a highly significant correlation between knowledge abilities and strategic abilities as well as that there is an increasing influence of knowledge abilities for competitive advantage through the center axes’ strategic abilities. The most important recommendation was to be on the Iraqi private banks to work on the integration of knowledge abilities and strategy combined in order to achieve a more competitive advantage than if used both individually Akaddrtin.